The community’s role in the coastal tourism economy of Yogyakarta, Indonesia - Rozaki, Zuhud; Man, Norsida; Sofani, Nadia; Hanawiyah Zuhra, Laras; Asiyah, Khuni; Fairuz Ramli, Mona; Shabudi Ariffin, Ahmad (Kasetsart University Faculty of International Maritime Studies, 2025)
The development of coastal tourism continues to grow, contributing both directly and indirectly to the local and national economy. The community plays an important role in coastal development. This study aims to assess the role of community in the coastal tourism economy. The research location is in Yogyakarta, covering three coastal tourism sites, namely Cemara Sewu Beach, Slili Beach, and Glagah Beach. As many as 180 respondents were surveyed through semi structured questionnaires, along with in-depth interviews conducted with nine key community leaders. This study focuses on the planning, organizing, implementing, and controlling involved in community management. The method used a combination of qualitative and quantitative approaches, also known as mixed methods. The findings indicate that the coastal community plays an important role in the growth of the tourism economy. The unique role of the coastal tourism community has a different character due to the characteristics and the location of the coast. The results show that awareness and active participation among economic actors, such as local traders and service providers, play a vital role in sustaining community-based tourism activities. Respondents indicated that their direct involvement in daily operations, such as managing services and maintaining facilities, is strongly influenced by how transparent and inclusive community leaders are during planning, implementation, and control processes. Sites with more open leadership structures, such as those integrating regular meetings and shared decision-making, reported higher levels of member participation across activities. The highest-rated community function was organizing, with mean score: 4.2, while planning had the lowest, with mean score 3.6, indicating a gap in strategic preparation. Additionally, external factors, such as government policies and tourist trends, also impact the community's role. Communities were found to be key actors in organizing tourism services, promoting environmental sustainability, and managing visitor experiences. This study offers a novel perspective by highlighting the integrated role of community-led planning and implementation in coastal tourism economies.